Nematicidal activity of furanocoumarins from parsley against Meloidogyne spp. Issue 8 (25th September 2014) - Caboni, Pierluigi; Saba, Marco; Oplos, Chrisostomos; Aissani, Nadhem; Maxia, Andrea; Menkissoglu‐Spiroudi, Urania; Casu, Laura; Ntalli, Nikoletta
Abstract BACKGROUND This report describes activity against Meloidogyne spp. and chemical characterisation of the essential oil and methanol extract of Petroselinum crispum aerial parts. The study was based on the hypothesis that P. crispum could be used as an intercrop and soil amendment in tomato culture for nematode control. RESULTS The methanol extract and the essential oil exhibited significant nematicidal activity against M. incognita, M. hapla and M. arenaria, the first being the most sensitive species, with EC50/72 h values of 140 ± 15 and 795 ± 125 mg L−1 for the extract and oil respectively. The most abundant furanocoumarin compounds in the methanolic extract were xanthotoxin, psoralen, bergapten and oxypeucedanin; levels ranged from 1.77 to 46.04 mg kg−1 wet weight. The EC50/24 h values of xanthotoxol, psoralen and xanthotoxin against M. incognita were 68 ± 33, 147 ± 88 and 200 ± 21 mg L−1 respectively. The addition of fresh parsley paste to soil reduced the number of M. incognita females and plant galls on tomato roots; EC50 values were 24.79 and 28.07 mg g−1 respectively. Moreover, parsley paste enhanced tomato growth in a dose–response manner. CONCLUSIONS Parsley exhibits promising nematicidal activity as an organic amendment and as a source of nematotoxic furanocoumarins. © 2014 Society of Chemical Industry